Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Nasabah PT. Bank BRI KC Balikpapan Sudirman - Dinda Natasya Amarty; Candraningrat Candraningrat (Global Leadership Organizational Research in Management, 2025)
This research aims to analyze the influence of service and product quality on the level of customer satisfaction of PT. Bank BRI KC Balikpapan Sudirman. Using a survey-based quantitative approach, this research involved 30 respondents as samples. The data obtained was analyzed using the multiple linear regression method using SPSS version 26 software. The research results show that service quality and product quality have a positive and significant impact on customer satisfaction. The regression coefficient for service quality was recorded at 0.313 with a significance level of 0.020, while the regression coefficient for product quality was 0.493 with a significance level of <0.001. The R Square value obtained is 0.537, indicating that 53.7% of the variation in customer satisfaction can be explained by these two variables, while the other 46.3% is influenced by factors outside this research model. These results confirm that product quality has a more dominant influence on customer satisfaction than service quality. Therefore, banks are advised to continue to innovate in developing product features and improving service quality through regular training for employees. This research provides a practical contribution to the banking sector in an effort to increase customer satisfaction and loyalty.